Thermophysical and rheological properties of dulce de leche with and without coconut flakes as a function of temperature - Barbosa, Vanessa Camarinha; Garcia-Rojas, Edwin Elard; Coimbra, Jane Sélia dos Reis; Cipriano, Paula de Aguiar; Oliveira, Eduardo Basílio de; Telis-Romero, Javier [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2013)
Doce de leite é uma sobremesa láctea concentrada (cerca de 70% de sólidos) muito apreciada no Brasil. Propriedades termofísicas e reológicas de duas formulações de doce de leite brasileiro (puro e adicionado de coco ralado a 1,5% em massa) foram determinadas a temperaturas compreendidas entre 28,4 e 76,4 °C. No geral, a presença de flocos de coco não acarretou diferenças significativas (p < 0,05) nestas propriedades das duas formulações. A capacidade calorífica variou entre (2633,2 e 3101,8) J/kg.°C; a condutividade térmica entre (0,383 e 0,452) W/m°C; a massa específica entre (1350,7 e 1310,7) kg/m³; e enfim, a difusividade térmica entre (1,082 × 10-7 e 1,130 × 10-7) m²/s. O modelo de Bingham descreveu adequadamente o comportamento não Newtoniano dos dois produtos, com tensão crítica de escoamento variando entre (27,3 e 17,6) Pa e a viscosidade plástica de (19,9 a 5,9) Pa.s.

Dulce de leche (DL), a dairy dessert highly appreciated in Brazil, is a concentrated product containing about 70% m/m of total solids. Thermophysical and rheological properties of two industrial Brazilian Dulce de leche formulations (classic Dulce de leche and Dulce de leche added with coconut flakes 1.5% m/m) were determined at temperatures comprised between 28.4 and 76.4 °C. In general, no significant differences (p < 0.05) were observed in the presence of coconut flakes in the two formulations. Heat capacity varied from 2633.2 to 3101.8 J/kg.°C; thermal conductivity from 0.383 to 0.452 W/m.°C; specific mass from 1350.7 to 1310.7 kg/m³; and, thermal diffusivity from (1.082 × 10-7 to 1.130 × 10-7) m²/s. The Bingham model was used to properly describe the non-Newtonian behavior of both formulations, with yielding stress values varying from 27.3 to 17.6 Pa and plastic viscosity from 19.9 to 5.9 Pa.s.
Propriedades termofísicas e reológicas de doces de leite puro e adicionado de flocos de coco em função da temperatura
Keywords: Bingham model; dulce de leche; Heat capacity; Thermal conductivity; specific mass; thermal diffusivity; modelo de Bingham; doce de leite; Capacidade calorífica; condutividade térmica; densidade; difusividade térmica